Making Room: cultural resistance through Pilimmaksarniq - Kathy Snow; Heather Ochalski (University of Aberdeen, School of Education, 2018)
The investigators and participants contributing to this research have been involved in a two year project examining the factors that impact student persistence and success in Inuit Nunangat (Inuit Homelands). Inuit Nunangat is the collective term used by the Inuit residing in the four land claims regions of Canada which geographically include, the Inuvialuit region in the Northwest Territories, Nunavut, Nunavik in northern Quebec and Nunatsiavut in Northern Labrador. Observations made from comments and activities in this project suggest that the integration of making modern and traditional crafts support cultural resilience in students and foster personal and professional success in their teachers. The data informing this research was gathered from participant comments at the Inuit Education Forum (held in Nain, February 2017) and five community case studies conducted across Inuit Nunangat in 2017-2018. The suggestion arising from narratives and observations of participants is that there is a greater need for the seamless integration of traditional making and skills in the formal education spaces because learning of these skills leads to greater Inuit identity development for youth, supports positive self-esteem, educational attainment and reduces gender barriers. This paper explores the relationship between traditional skills development and schools as a means to bridge the distance between Inuit and southern traditions of education. Imbedded in this discussion is the concept of Pilimmaksarniq (the development of skills through observation, mentoring, practice and effort) as resistance to formal industrial format curriculum.